Subliminal Priming Effects of Masked Social Hierarchies During a Categorization Task: An Event-Related Brain Potentials Study - Fondevila, Sabela; Hernández-Gutiérrez, David; Espuny, Javier; Jimenez-Ortega, Laura; Casado, Pilar; Muñoz, Francisco Muñoz; Sánchez-García, José; Martín-Loeches, Manuel (Frontiers in Human Neuroscience, 2022)
Evidence so far shows that status detection increases attentional resources, especially for high hierarchies. However, little is known about the effects of masked social status cues on cognition. Here, we explore masked priming effects of social status cues during a categorization task. For this purpose, we use Event-Related brain Potentials (ERP) time-locked to the presentation of two types of artworks (Christian, non-Christian) primed by masked social hierarchies sorted into two types (religious, military), and in two ranks (high, low) each. ERP results indicate early attention effects at N1, showing larger amplitudes for the processing of artworks after high and military ranks. Thereafter, the P3a increased for all artworks primed by religious versus military figures, indicating a relevant role of task demands at this processing stage. Our results remark the automaticity of hierarchy detection and extends previous findings on the effects of social status cues on complex cognitive processes.